2019
DOI: 10.1001/jamapediatrics.2019.0032
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-effectiveness of Antenatal Corticosteroid Therapy vs No Therapy in Women at Risk of Late Preterm Delivery

Abstract: IMPORTANCE Administration of corticosteroids to women at high risk for delivery in the late preterm period (34–36 weeks’ gestation) improves short-term neonatal outcomes. The cost implications of this intervention are not known. OBJECTIVE To compare the cost-effectiveness of treatment with antenatal corticosteroids with no treatment for women at risk for late preterm delivery. DESIGN, SETTING, AND PARTICIPANTS This secondary analysis of the Antenatal Late Preterm Steroids trial, a multicenter randomized cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…A large randomized trial study concerning ACS treatment, involving 1427 ACS-treated and 1400 placebo-treated pregnant women who gave birth at 34 (0/7) to 36 (6/7) gestation, found use of ACS for pregnant women, could decrease the incidence of severe respiratory complications of preterm infants, but had no in uence on the use of mechanical ventilation for preterm infants and the incidence of neonatal sepsis. The above ndings are consistent with our research [8,10].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A large randomized trial study concerning ACS treatment, involving 1427 ACS-treated and 1400 placebo-treated pregnant women who gave birth at 34 (0/7) to 36 (6/7) gestation, found use of ACS for pregnant women, could decrease the incidence of severe respiratory complications of preterm infants, but had no in uence on the use of mechanical ventilation for preterm infants and the incidence of neonatal sepsis. The above ndings are consistent with our research [8,10].…”
Section: Discussionsupporting
confidence: 93%
“…There are positive and negative views on ACS treatment for women at high risk of giving birth at 34 (0/7) to 36 (6/7) weeks. The positive view indicates that ACS treatment can decrease incidence of neonatal respiratory distress syndrome (NRDS) and neonatal hospitalization expenses in preterm infants between 34 (0/7) to 36 (6/7) weeks gestation [8][9][10]. The negative view indicates that this treatment does not reduce respiratory disease and wet lung in late preterm infants, but increases incidence of neonatal hypoglycemia and neonatal sepsis [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous trials demonstrated an improvement in neonatal respiratory outcomes with betamethasone, followed by a significant reduction in RDS in late preterm infants exposed to antenatal steroids [ 18 ] and a decrease in health care costs [ 19 ]. However, these studies included all LPT births, regardless of various causes of preterm birth or PPROM.…”
Section: Discussionmentioning
confidence: 99%
“…94 The cost-effectiveness of the administration of betamethasone based in individual trials is controversial, and it should be based in the best estimation of effectiveness. 95,96 Mainly LMICs still have significant challenges to provide safe and effective antenatal corticosteroid use, including ensuring accurate gestational age determination, establishing clear treatment guidelines, strengthening provider capacity, incorporating corticosteroid in national essential medicines lists, and monitoring use and outcomes. 97…”
Section: Discussionmentioning
confidence: 99%